Enabling factors and support mechanisms in the emergence of inclusive organisational brand leadership optimal for innovation and change - Mahoney, Wendy (IIE Emeris, 2026)
This study explores inclusive leadership as the style that shapes organisational brand cultures suited for innovation and change. These cultures navigate complexity and enable adaptable employees who drive stakeholder-centric innovation. Stakeholder-centric innovation is the key challenge for organisations today. Organisational brand cultures result from leadership influence, not isolated branding efforts. This study reframes organisational brand leadership as leadership. It explores inclusive leadership to enable inclusive organisational brand leadership. Organisational brand leaders lack sufficient guidance to integrate inclusion into their practices. This gap blocks inclusive organisational brand leadership and threatens innovation, equity, and sustainability. The study bridges this gap by examining inclusive leadership to support inclusive organisational brand leadership. The study uses an exploratory qualitative design with interpretivist epistemology and constructivist ontology. It explores lived experiences through semi-structured interviews with 23 leaders recognised by Business Engage (NPC) for inclusion. This process creates an interpretive theory of the inclusion journey. Inclusive empathy forms the core of inclusive leadership. The study introduces the Inclusive Empathy Model, a guide to, and reconceptualisation of inclusive leadership. Inclusive leadership relies on inclusive empathy, respect, authenticity, and Emotional Intelligence (EI). These elements drive collaborative and stakeholder-centric innovation. Authenticity, based on self-awareness and self-acceptance, builds trust, adaptability, creativity and innovation. It creates belonging for all individuals. The study led to the development of the Sequential Journey to Inclusive Organisational Brand Leadership Model as a roadmap for this process. Organisations are urged to embed inclusion in brand cultures via inclusively empathetic leadership. This approach manages change, builds competitive advantage, and supports a connected future. Inclusive organisational brand leadership requires training, coaching, and mentorship. The study shows that the cultivation of inclusive organisational brand leadership requires the internal transformation of leaders. This enables a new type of organisational brand leader to support inclusion, stakeholder-centric innovation, better business, and a better world.
Keywords: Innovative work behaviour; Internal brand building; Organisational brand leadership; Inclusive leadership; Leading for change; Inclusive empathy